Analisa Pengaruh Rasio Keuangan Terhadap Pertumbuhan Harga Saham Bank Buku IV Yang Terdaftar Di Bursa Efek Indonesia - Fralus Dolfy Ellyson; Mahjus Ekananda Sitompul; Etty Puji Lestari (Cakrawala Repositori IMWI, 2023)
Research on the effect of financial ratios on stock prices has been carried out on various research objects, but specifically examining the effect of financial ratios specifically on the growth of BUKU IV bank stock prices has never been done so that research is needed to reveal what the effect of financial ratios consisting of Net Profit Margin ( NPM), Return On Equity (ROE), Debt to Equity Ratio (DER) and Current Ratio (CR) to the growth of BUKU IV bank stock prices. The research sample was taken from banking companies in the BUKU IV category as many as 7 companies that have been listed on the Indonesia Stock Exchange for the period 2017 to 2019. The sampling method was purposive sampling using secondary data in the form of quarterly financial reports published through the Indonesia Stock Exchange website. The data were analyzed using the E-views econometrics program version 10. through the estimation stages of panel data regression model selection, normality test, heteroscedasticity test, multicollinearity test and then hypothesis testing. The results showed that partially Net Profit Margin (NPM) and Debt to Equity Ratio (DER) had a significant effect on stock price growth, while Return On Equity (ROE) and Current Ratio (CR) did not. significant effect on the growth of BUKU IV bank stock prices. However, simultaneously Net Profit Margin (NPM), Return On Equity (ROE), Debt to Equity Ratio (DER) and Current Ratio (CR) have no effect on the growth of BUKU IV bank stock prices, so there are other independent variables that are not included in the study which affect the growth of stock prices.